Students’ Perception on Teachers’ Bilingual Language in English Language Teaching - Anugrah Murtini Anugrah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Bilingual language in English language teaching (ELT) refers to the pedagogical approach where subjects are taught in both a student's native language (L1) in this case Indonesian and the target language, English (L2). This study aimed to find out the students’ perception about the use of bilingual language by the teacher in class XI at SMAN 9 Pangkep. The researcher used a mixed-method approach, integrating both quantitative and qualitative data to provide a more comprehensive understanding of the research questions. The data was collected through observation, questionnaires, and interviews. The participants of questionnaire involved 83 students and 10 students in interview, they are from XI grade in SMAN 9 Pangkep. South Sulawesi. The findings revealed that students had positive perceptions of the teacher’s use of bilingual language during the class, it facilitated their learning of English, making it easier for them to understand the material, enhanced their English skill, contributed to a more comfortable classroom environment and enhanced students' confidence to participate actively in class discussions.